Using impact modulation to quantify nonlinearities associated with bolt loosening with applications to satellite structures. (1st February 2019) - Meyer, Janette J.; Adams, Douglas E.
Highlights: Recent advancements in satellite technology have resulted in the development of quickly-built, modular satellites that can be designed, built, tested, and launched within days of when their need is established. One consequence of the short time frame during which these satellites are prepared for launch is the increased possibility of having loose bolts within the assembly. Loose bolts are undesirable because they increase the risk of damage during launch and, therefore, a method for identifying the presence of loose bolts within the satellite structure is required. In this paper, the effectiveness of using impact modulation testing to detect loose bolts within a structure is investigated. Four structures with increasing geometric complexity are tested: a three-beam, two-bolt assembly; a four-beam, three-bolt assembly; a satellite panel; and a full satellite structure. Impact modulation results are quantified using an integration-based metric. The value of the metric is shown to increase as the torque on one or more of the bolts within each structure decreases. Results from all four structures showed that torque loss of 50% or more resulted in a change in the metric value of at least 20%. Abstract: Recent advancements in satellite technology have resulted in the development of quickly-built, modular satellites that can be designed, built, tested, and launched within days of when their need is established. One consequence of the short time frame during which these satellites are prepared for launch is the increased possibility of having loose bolts within the assembly. Loose bolts are undesirable because they increase the risk of damage during launch and, therefore, a method for identifying the presence of loose bolts within the satellite structure is required. In this paper, the effectiveness of using impact modulation (IM) testing to detect loose bolts within a structure is investigated. Four structures with increasing geometric complexity are tested: a three-beam, two-bolt assembly; a four-beam, three-bolt assembly; a satellite panel; and a full satellite structure. IM results are quantified using an integration-based metric. The value of the metric is shown to increase as the torque on one or more of the bolts within each structure decreases. Results from all four test cases showed that torque loss of 50% or more with respect to the fully tightened, baseline torque level resulted in a change in the metric value of at least 20% from its baseline value.